2011
DOI: 10.4314/thrb.v13i3.63671
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of ultrasound in the diagnosis of bladder tumours at the Muhimbili National Hospital, Dar es Salaam, Tanzania

Abstract: Abstract:The importance of an ultrasound in diagnosis of bladder tumours has been investigated by different authors. Some have questioned its effectiveness while others have considered the technique to be an important tool in the initial evaluation of bladder tumours. This study was carried out to establish the effectiveness of the ultrasound in diagnosis of bladder tumours at the Muhimbili National Hospital in Dar es Salaam, Tanzania. Clinical indications and ultrasound findings were recorded. Cystoscopy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…In another study carried out by Mwashambwa et al ., the sensitivity and the specificity of sonography in diagnosing bladder tumors were, respectively, 83% and 93% and both positive and negative predictive values were 89%. [ 15 ] The results of that study are lower than those of the present study; specificity was reported to be 100% in the current study. Since specificity is significant in determining the validity a test, the results of the present study are more reliable, and since sonography is a highly operator-dependent test, the difference between the two studies can be attributed to the differences in the operators’ experiences in the two studies.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In another study carried out by Mwashambwa et al ., the sensitivity and the specificity of sonography in diagnosing bladder tumors were, respectively, 83% and 93% and both positive and negative predictive values were 89%. [ 15 ] The results of that study are lower than those of the present study; specificity was reported to be 100% in the current study. Since specificity is significant in determining the validity a test, the results of the present study are more reliable, and since sonography is a highly operator-dependent test, the difference between the two studies can be attributed to the differences in the operators’ experiences in the two studies.…”
Section: Discussioncontrasting
confidence: 87%
“…[ 14 ] In another study carried out by Mwashambwa et al ., the sensitivity and the specificity of sonography in diagnosing bladder tumors were respectively, 83% and 93%. [ 15 ] Despite promising results, however, studies in this field have not yet become common; therefore, the present study was conducted to investigate the role of ultrasound in diagnosis and examination of bladder tumors.…”
Section: Introductionmentioning
confidence: 99%